Does polygenic risk influence associations between sun exposure and melanoma? A prospective cohort analysis. (1st August 2020) - Olsen, C.M.; Pandeya, N.; Law, M.H.; MacGregor, S.; Iles, M.M.; Thompson, B.S.; Green, A.C.; Neale, R.E.; Whiteman, D.C.; ,
Summary: Background: Melanoma develops as the result of complex interactions between sun exposure and genetic factors. However, data on these interactions from prospective studies are scant. Objectives: To quantify the association between ambient and personal ultraviolet exposure and incident melanoma in a large population‐based prospective study of men and women residing in a setting of high ambient ultraviolet radiation, and to examine potential gene–environment interactions. Methods: Data were obtained from the QSkin Sun and Health Study, a prospective cohort study of men and women aged 40–69 years, randomly sampled from the Queensland population in 2011. Participants were genotyped and assessed for ultraviolet exposure. Results: Among participants with genetic data ( n = 15 373), 420 (2·7%) developed cutaneous melanoma (173 invasive, 247 in situ ) during a median follow‐up time of 4·4 years. Country of birth, age at migration, having > 50 sunburns in childhood or adolescence, and a history of keratinocyte cancer or actinic lesions were significantly associated with melanoma risk. Conclusions: An interaction with polygenic risk was suggested: among people at low polygenic risk, markers of cumulative sun exposure (as measured by actinic damage) were associated with melanoma. In contrast, among people at high polygenic risk, markers of high‐level early‐life ambient exposure (as measured by place of birth) were associated with melanoma (hazard ratio for born in Australia vs. overseas 3·16, 95% confidence interval 1·39–7·22). These findings suggest interactions between genotype and environment that are consistent with divergent pathways for melanoma development. What's already known about this topic? The relationship between sun exposure and melanoma is complex, and exposure effects are highly modified by host factors and behaviours. The role of genotype on the relationship between ultraviolet radiation exposure and melanoma risk is poorly understood. What does this study add? We found that country of birth, age at migration, sunburns in childhood or adolescence, and history of keratinocyte cancer or actinic lesions were significantly associated with melanoma risk, while other measures of continuous or more intermittent patterns of sun exposure were not. We found evidence for gene–environment interactions that are consistent with divergent pathways for melanoma development. Linked Comment: Cust. Br J Dermatol 2020; 183:205–206 .